Development of AR training systems for Humanitude dementia care. (3rd April 2022) - Kurazume, Ryo; Hiramatsu, Tomoki; Kamei, Masaya; Inoue, Daiji; Kawamura, Akihiro; Miyauchi, Shoko; An, Qi
Abstract : This paper presents a comparative study of two AR training systems for Humanitude dementia care. Humanitude is a multimodal comprehensive care methodology for patients with dementia and has attracted considerable attention as a gentle and effective care technique. To provide an effective training system for Humanitude, we developed HEARTS 1, which realizes simultaneous sensing and interaction by combining a real training entity and augmented reality technology. However, training experiments using HEARTS 1 indicated that HEARTS 1 had certain weaknesses that should be addressed, namely, the usability of the AR display or the impression of the CG model. This paper presents a new prototype called HEARTS 2 consisting of Microsoft HoloLens 2 as well as realistic and animated CG models of older women. Psychological experiments were conducted to identify the difference in the usability of the AR displays, such as the weight and the field of view, and the impression of the CG models. We also conducted questionnaire surveys for beginners and medical professionals and preliminary training experiments to evaluate the usefulness of HEARTS 2. Based on the psychological experiments and questionnaire surveys, we concluded that HEARTS 2 was more comfortable and suitable for a training system for dementia care. GRAPHICAL ABSTRACT: UF0001